2011
DOI: 10.1016/j.beem.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control in non-diabetic critically ill patients

Abstract: Hyperglycemia is a common and costly health care problem in hospitalized patients. In hospital hyperglycemia is defined as any glucose value >7.8 mmol/l (140 mg/dl). Hyperglycemia is present in 40% of critically ill patients and in up to 80% of patients after cardiac surgery, with ~ 80% of ICU patients with hyperglycemia having no history of diabetes prior to admission. The risk of hospital complications relates to the severity of hyperglycemia, with a higher risk observed in patients without a history of diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 86 publications
4
87
0
9
Order By: Relevance
“…Stress hyperglycemia can occur in hospitalized patients without a previous history of DM and is defined as any serum glucose > 140 mg/dL. Although this hyperglycemic state typically resolves with abatement of the heightened stress, approximately 60% of patients may ultimately develop DM [7] . Surgery, trauma and infection stimulate release of counter regulatory hormones such as glucagon, epinephrine, cortisol, and growth hormone, resulting in derangement in normal carbohydrate metabolism.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Stress hyperglycemia can occur in hospitalized patients without a previous history of DM and is defined as any serum glucose > 140 mg/dL. Although this hyperglycemic state typically resolves with abatement of the heightened stress, approximately 60% of patients may ultimately develop DM [7] . Surgery, trauma and infection stimulate release of counter regulatory hormones such as glucagon, epinephrine, cortisol, and growth hormone, resulting in derangement in normal carbohydrate metabolism.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Surgery, trauma and infection stimulate release of counter regulatory hormones such as glucagon, epinephrine, cortisol, and growth hormone, resulting in derangement in normal carbohydrate metabolism. This dysfunction may result in a decrease in peripheral tissue insulin uptake (i.e., resistance), gluconeogenesis in the liver, decreased efficiency of tissue glucose utilization and relative insulin deficiency [7] . Both observational studies and prospective studies in intensive care unit (ICU) patients have demonstrated a correlation between hyperglycemia and adverse outcomes during the hospitalization [8,9] .…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…В настоящее время именно адекватный контроль глюкозы считается первостепенно важным [42]. Известно, что контроль ГГ уменьшает стационарные осложнения и летальность; однако оптимальный целевой уровень гликемии до сих пор обсуждается [43], а протоколы введения инсулина отличаются по целевым показателям и пороговым зна-чениям, при которых нужно начинать инсулинотерапию. Принципиально существует два лагеря, один из которых придерживается необходимости «жесткого контроля», другой ориентирован на менее интенсивную коррекцию.…”
Section: результаты при различных протоколахunclassified
“…Принципиально существует два лагеря, один из которых придерживается необходимости «жесткого контроля», другой ориентирован на менее интенсивную коррекцию. «Жесткий» протокол контроля предполагает поддержа-ние уровня глюкозы крови в интервале 4,5-6 ммоль/л, инфузию инсулина рекомендовано начинать при уровне более 6 ммоль/л, менее интенсивный протокол реко-мендует интервал 8-10 ммоль/л, инфузию начинают при уровне более 10 ммоль/л [43].…”
Section: результаты при различных протоколахunclassified